Slovenski periodični tisk in izbrane strokovne knjige do 1820 - Bošnjak, Blanka (Jezik in slovstvo, 2020)
In the context of the first Slovenian periodicals and the publication of Slovenian professional books (meaning secular prints) published by 1820, their important role in educating Slovenians would be highlighted from Trubar's calendar onwards, which was first published in 1557. In the eighteenth century, periodical editions of various useful and instructive almanacs for management followed - Nova krajnska pratika (from at least 1726 onwards), Breznik's Večna pratika od gospodarstva (first from 1789) - and from that time Vodnik's Velika and Mala pratika appeared at the turn of the century with upgraded content. The publication of other Slovenian professional books of a popular nature flourished, especially during the Enlightenment, in accordance with its utilitarian doctrine and the tendency to inform. Among such publications was the first Slovenian newspaper, Lublanske novice.
Keywords: almanacs; časopisi; history of Slovene literature; Lublanske novice; newspapers; pratike; Slovenian calendars; Slovenian professional books; slovenske strokovne knjige; slovenski koledarji; zgodovina slovenskega slovstva